Counseling on the Provision of Complementary Breastfeeding Against Constipation in Babies in the Baru Village of Ladang Bambu, Medan Tuntungan Sub-district in 2021 - Rizky. A Bakara; Nurdiana Manurung (Science Midwifery, 2021)
The purpose of this study was to find out whether mothers understand about complementary feeding and mothers know if their babies are constipated. And the activities carried out were to increase the mother's knowledge when her baby was constipated which was marked by crying, whining in pain and the face turning red before defecation giving MP ASI. Increasing mother's knowledge about the types of MP ASI for babies. the following is the provision of material to mothers regarding constipation in infants, and complementary feeding for giving snacks to infants. The results of the research are To achieve the objectives of the above activities, activities are carried out including the delivery of material about constipation in infants, and MP ASI.